PENGARUH INDEPENDENSI, PENGALAMAN KERJA DAN PROFESIONALISME BADAN PENGAWAS TERHADAP EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL PADA LPD KECAMATAN GIANYAR - Gusti Ayu Diah Vicha Ananda; Sang Ayu Putu Arie Indraswarawati; Cokorda Gede Bayu Putra (Hita Akuntansi dan Keuangan, 2021)
The aim of this research is to get empirical evidence about the effect of independence, work experience and professionalism of the internal controllers on the effectiveness of the internal control system LPD in Gianyar district. The sample in this study was 16 LPDs in Gianyar with 48 respondents. The sampling method uses the census method, so that the number of samples is equal to the population, which is 48 regulatory people. The research data was collected using a questionnaire. Data were analyzed with Descriptive Statistical Analysis, Validity Test, Classic Assumption Test Reliability Test, F Test, T Test, and Multiple Linear Regression Analysis. The results of this study indicated that the independence variable (X1) had no effect on the effectiveness of the internal control system, the work experience variable (X2) had a positive and significant effect on the effectiveness of the internal control system, and the professionalism variable (X3) had no effect on the effectiveness of the internal control system.